Clinical characteristics of sarcopenia in patients with alcoholic liver cirrhosis - Chisato Saeki (JGH Open, 2021)
Abstract Background and Aim Sarcopenia frequently develops in patient with liver cirrhosis (LC). Ethanol reduces muscle protein synthesis and accelerates proteolysis. However, the relationship between heavy alcohol consumption and sarcopenia remains controversial. This study aimed to investigate the characteristics and prevalence of sarcopenia among patients with alcoholic LC (ALC) in real‐world clinical settings. Methods This cross‐sectional study included 181 patients with LC. Heavy alcohol consumption was defined as >60 g/day. Sarcopenia was diagnosed according to the Japan Society of Hepatology criteria. Results Among the 181 patients, 64 (35.4%) were diagnosed with ALC. Patients with ALC were younger (median, 61.5 vs 72.0 years; P < 0.001) and had a lower prevalence of sarcopenia (18.8 vs 32.5%; P = 0.048) than those with non‐ALC. Conversely, the former had a higher prevalence of Child–Pugh class B/C (P = 0.015), higher total bilirubin (P = 0.017), and lower prothrombin time (P < 0.001) than the latter. The prevalence of sarcopenia increased alongside advancing age in patients with ALC (P = 0.007). Multivariate analysis identified older age (but not disease stage/liver function reserve and alcohol consumption) as an independent factor associated with sarcopenia (P = 0.002) in patients with ALC. Conclusion Patients with ALC were younger and had a lower prevalence of sarcopenia, despite advanced disease stage/impaired liver function reserve, compared to those with non‐ALC in real‐world clinical settings. However, older age was strongly associated with sarcopenia, even in patients with ALC. There was no significant influence of heavy alcohol consumption on the development of sarcopenia.